IMPROVING THE STUDENTS’ READING COMPREHENSION BY USING COMIC STRIPS AT SMAMUHAMMADIYAH-7 SERBELAWAN GRADE XI - Bennarita Purba; Mustika Rini (Program Studi Pendidikan Bahasa Inggris FKIP, 2021)
This Research entitled improving the students’ reading comprehension by using comic strips at SMA MUHAMMADIYAH-7 Serbelawan. It concerned with the problem: Does comic strips effective to improve students’ reading comprehension through narrative text at the eleventh grade of SMA MUHAMMADIYAH-7 Serbelawan?. To answer the research problem, some theories are used: Kligner, Vaughn & Boardman (2007), to Patel and Jain (2008), Snow (2002), Arikunto(2009,2010). Reading is basic skills which should be studied are speaking, listening, reading and writing and a process of looking at series of written symbols and getting meaning from them. Comic strips is some series of drawing that tell a story and drawings interrelated panels to display brief humor or form a narrative often serialized with text in balloons and captions and with the comic strips can improve reading comprehension of students in English. This research is designed into quantitative research by following experimental design of control class and experimental class. The population is 216 students and the sample is taken by using cluster sampling technique so that the sample is 72 students. The research subject is XI IPA1 as experimental class and XI IPA2 as control class of SMA MUHAMMADIYAH-7 Serbelawan. Research instrument is multiple choices. The data analysis is started from scoring the students’ answer sheet, tabulating students’ pre-test and post-test scores, calculating the standard deviation pre-test and post-test scores. Based on the data analysis, it was found before the treatment of using comic stripsvalue pre-test was 1904 and mean (average) was 52,88 in post-test get value was 2132 and mean (average) was 59,22 and the standard deviation pre-test was 10,20 and post-test was 10,01. get value pre-test was 1972 and mean (average) was 54,78 in post-test value was 3004 and mean (average) was 83,45 and the standard deviation pre-test was 6,91 and post-test was 6,93. Using comic strips effective in improvingstudents’ reading comprehension through narrative text at the eleventh grade of SMA MUHAMMADIYAH-7 Serbelawan. The t-table value is on the amount sample (n) 72 subtracted 2 then the number of sample will be 70 which the value of t-table was 1,99. Then, result was df(degree of freedom) =70. So, the t-test result was than 5,73> 4,22 >1,99. It can be concluded that result of experimental class more of control class result that the researcher was accepted